THE RELATIONSHIP BETWEEN SMARTPHONE USE INTENSITY AND SLEEP QUALITY IN ADOLESCENTS IN GRADES X AND XI AT STATE SENIOR HIGH SCHOOL 1 KRAMATWATU - Anggi putriani; Alif Nurul Rosyidah; Osep Yasier Almunsiri (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Background: Adolescence is a transitional period from childhood to adulthood, beginning at the onset of puberty and continuing until maturity is reached. The use of smartphones can have both positive and negative impacts on teenagers. On the positive side, teenagers have access to resources for learning, the ability to communicate remotely, and the opportunity to learn online. On the other hand, they may experience a decrease in physical activity, which can lead to laziness in studying, eye strain, and disturbances in sleep quality. Objective: This study aims to determine the relationship between smartphone usage intensity and sleep quality among 10th and 11th grade students at SMAN 1 Kramatwatu. Method: This research employs a quantitative study design with a cross-sectional approach involving 261 respondents from SMAN 1 Kramatwatu. There are a total of 592 students in 10th and 11th grades, with 300 students in 10th grade and 292 students in 11th grade. The sampling method used is probability sampling, specifically simple random sampling. Respondents from each class were selected using the Stratified Random Sampling formula. Data were analyzed using the chi-square statistical test. Result: The univariate analysis revealed that the majority of respondents were in mid-adolescence, totaling 233 respondents (85.4%). Based on gender, most respondents were male, totaling 177 respondents (67.8%). The chi-square test analysis indicated a statistically significant relationship between smartphone usage intensity and sleep quality among adolescents, with a P value of 0.000. Conclusion: There is a significant relationship between smartphone usage intensity and sleep quality among adolescents.